Properties of paper sludge filled polypropylene (PP)/ethylene propylene diene terpolymer (EPDM) composites: The effect of silane-based coupling agent - Salmah Husninsyah; Hanafi, A. Ismail; Azuraliza, Abu Bakar (Taylor & Francis, 2009)
Link to publisher's homepage at